Global burden of ischemic heart disease in older adult populations linked to non-optimal temperatures: past (1990–2021) and future (2022–2050) analysis - Liu, Lihui; He, Yisong; Huang, Gang; Zeng, Yangxi; Lu, Jiaan; He, Ru; Chen, Haiqing; Gu, Yuheng; Hu, Qingwen; Liao, Bin; Wan, Juyi (Frontiers in Public Health, 2025)
BackgroundIschemic heart disease (IHD) is a leading cause of death and disability, particularly affecting the older adult population. Extreme temperatures, especially very low and very high temperatures, are known to exacerbate cardiovascular disease burden. With the ongoing global climate change, understanding the impact of non-optimal temperatures on IHD burden becomes increasingly important, especially in vulnerable populations such as the older adult.MethodsThis study used data from the Global Burden of Disease Study 2021 (GBD 2021) to analyze the spatiotemporal trends of low and high temperatures on IHD burden in the older adult population (aged 60 and above) from 1990 to 2021. We used age-standardized rates (ASR), annual percentage change (EAPC), and the Bayesian age-period-cohort (BAPC) model to forecast 2050. Additionally, the geographic differences in IHD burden were analyzed using World Bank regions.ResultsFrom 1990 to 2021, the IHD burden in the older adult population was mainly attributed to low temperatures. However, it has increased the burden of IHD due to high temperatures, especially in tropical and low-income regions. The analysis of gender difference revealed that men are usually more affected by high temperatures, though generally, women are more sensitive to low temperatures. Forecasts are that in the future, the burden of IHD due to high temperatures will continue to rise, especially in areas with limited adaptive capacity.ConclusionAlthough low temperature remains the most important contributor to IHD burden among the older adult, the burden attributable to high temperature is on the rise, which increases the need to address the extreme temperature fluctuation. That is more so in poor-income and tropical regions where the most vulnerable populations bear a higher risk for health. Thus, there is an urgent need to develop adaptive public health measures against the dual health risks from extreme temperatures. The findings emphasize that targeted interventions are necessary, with adjustments in regional differences and gender-specific risks to effectively address the growing health threats from climate change.